Population pharmacokinetics of polymyxin B in critically ill patients with carbapenem-resistant organisms infections: insights from steady-state trough and peak plasma concentration - Yang, Jun; Yu, Mingjie; Gan, Yu; Cheng, Lin; Yang, Ge; Xiong, Lirong; Liu, Fang; Chen, Yongchuan (Frontiers in Pharmacology, 2025)
AimsTo establish a population pharmacokinetic (PopPK) model of polymyxin B (PMB) in critically ill patients based on steady-state trough (Ctrough,ss) and peak (Cpeak,ss) concentrations, optimize the dosing regimen, and evaluate the consistency of 24-hour steady-state area under the concentration-time curve (AUCss,24h) estimation between model-based and the two-point (Ctrough,ss and Cpeak,ss) methods.MethodsPopPK modeling was performed using NONMEM, Monte Carlo simulations were used to optimize PMB dosing regimens. Bland-Altman analysis was used to evaluate the consistency between the two AUCss,24h estimation methods.ResultsA total of 95 patients, contributing 214 blood samples, were included and categorized into a modeling group (n = 80) and a validation group (n = 15). A one-compartment model was developed, with creatinine clearance (CrCL) and platelet count (PLT) identified as significant covariates influencing PK parameters. Simulation results indicated that when a Minimum Inhibitory Concentration (MIC) ≤ 0.5 mg·L-1, a probability of target attainment (PTA) ≥ 90% was achieved in all groups except for the 50 mg every 12 h (q12h) maintenance dose group. PTA decreased as CrCL increased, with slight variations observed across different PLT levels. The 75 mg and 100 mg q12h groups showed a higher proportion of AUCss,24h within the therapeutic window. Bland-Altman analysis revealed a mean bias of 12.98 mg·h·L-1 between the two AUCss,24h estimation methods. The Kappa test (κ = 0.51, P < 0.001) and McNemar’s test (P = 0.33) demonstrated moderate agreement, reflecting overall consistency with minor discrepancies in classification outcomes.ConclusionThe PopPK model of PMB is well-suited for critically ill patients. The 75 mg q12h and 100 mg q12h regimens are appropriate for critically ill patients, with CrCL levels guiding individualized dosing. A two-point sampling strategy can be used for routine therapeutic drug monitoring (TDM) of PMB.